Counting missing women - A reconciliation of the "flow measure" and the "stock measure" - Cara Ebert; Stephan Klasen; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Existing estimates of the 'stock of missing women' suggest that the problem is mostly concentrated in South and East Asia, and often related to sex-selective abortions and postbirth neglect of female children. In contrast, estimates of yearly excess female deaths, referred to as the 'flow of missing women', suggest that gender bias in mortality is much larger than previously found (about 4 to 5 million excess female deaths per year vs. around 100 million missing women in total), is as severe among adults as it is among children in India, and is larger in Sub-Saharan Africa than in South and East Asia. We argue that these findings largely rely on the choice of the reference standard for sex-specific mortality and an incomplete correction for different disease environments in the flow measure. When alternative reference standards are used, the results of the flow measure can be reconciled with previous findings of the stock measure.
Keywords: J16; D63; I10; 330; Missing women; gender bias; mortality; disease; age; Sub-Saharan Africa; China; India